2004
DOI: 10.1177/0363546504263151
|View full text |Cite
|
Sign up to set email alerts
|

Tunnel Enlargement after Anterior Cruciate Ligament Surgery

Abstract: Bone tunnel enlargement has been reported after anterior cruciate ligament (ACL) reconstruction surgery. Although the long-term outcome of this phenomenon is not yet known, tunnel lysis or expansion may be clinically significant in revision surgery because the enlarged tunnels may complicate graft placement and fixation. There any many proposed theories for tunnel lysis. The most accurate statement is that this condition has a multifactorial etiology. Mechanical and biological causes have been reported, and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
206
1
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(221 citation statements)
references
References 49 publications
(151 reference statements)
4
206
1
10
Order By: Relevance
“…Tunnel widening after anterior cruciate ligament (ACL) reconstruction is a well-described phenomenon. 8 The basis of tunnel widening is multifactorial, with several possible mechanical and biological contributing factors. 9 Among the possible causes, mechanical factors such as graft tunnel motion, stress deprivation of bone within the tunnel wall, improper graft tunnel placement, tunnel positioning, graft fixation method, resorbable implant degradation, access of joint fluid to the graft-bone interface, and bone quality and aggressive rehabilitation have been considered.…”
Section: Discussionmentioning
confidence: 99%
“…Tunnel widening after anterior cruciate ligament (ACL) reconstruction is a well-described phenomenon. 8 The basis of tunnel widening is multifactorial, with several possible mechanical and biological contributing factors. 9 Among the possible causes, mechanical factors such as graft tunnel motion, stress deprivation of bone within the tunnel wall, improper graft tunnel placement, tunnel positioning, graft fixation method, resorbable implant degradation, access of joint fluid to the graft-bone interface, and bone quality and aggressive rehabilitation have been considered.…”
Section: Discussionmentioning
confidence: 99%
“…Functional clinical assessment scores did not demonstrate any significant differences, which may be due to the relatively low sensitivity and specificity demonstrated for clinical scores in the detection of minimal changes [17]. HGCS hamstring graft condition score Additional BPA could not prevent femoral TW although a reduction of interface micromotion, which is the predominant aetiological factor in theories on TW [10], due to superior biomechanical properties has been suggested. Several authors found fixation constructs augmented with cancellous bone plugs had higher stiffness values and pullout forces than fixation constructs alone [6,11].…”
Section: Discussionmentioning
confidence: 92%
“…at the time when TW occurs [18,19]. In that instance, TW was the result of stronger mechanical and biological mechanisms [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It results in potential higher knee laxity that could be an early sign of a bad postoperative result. Bone resorption and osteolytic processes in this area are the reasons for tunnel widening [24]. There is growing evidence that interleukin-1β (IL-1β) plays an important role in the pathogenesis of bone tunnel enlargement following ACL reconstruction [7,13,16].…”
mentioning
confidence: 99%